The Design and Rationale of a Multicentre Randomised Controlled Trial Comparing Transperineal Percutaneous Laser Ablation With Transurethral Resection of the Prostate for Treating Benign Prostatic Hyperplasia - Zhang, Wei; Zhang, Weituo; Guo, Qian; Chen, Lei; Meng, Zheying; Xu, Yanjun; Cao, Nailong; Hu, Bing; Qian, Biyun (Frontiers in Surgery, 2021)
Background Transurethral resection of the prostate (TURP) is regarded as the ‘‘gold standard’’ for the treatment of benign prostatic hyperplasia(BPH) in elderly men. However, approximately 15% of patients who had undergone TURP had intraoperative and postoperative complications, such as bleeding, electrolyte balance disorder and urethral stricture. Transperineal percutaneous laser ablation (TPLA) is a method that places the optical fibre directly into the prostate with the guidance of ultrasound imaging, and the percutaneous transperineal approach is performed distal to the urethra and rectum to protect these structures and reduce urethral or postoperative infection. Several studies on TPLA for BPH treatment have been reported recently; however, high-quality randomized controlled trial (RCT) to evaluate its efficacy, safety and long-term follow up remain absent. Methods This study is a multicentre, open-label RCT to assess the efficacy and safety of TPLA versus TURP to treat BPH. We hypothesise that the TPLA has non-inferior efficacy to TURP in the International Prostate Symptom Score (IPSS ) at 3 months changing from the baseline and lower incidence of post-surgery complications. One hundred and fourteen patients with BPH will be recruited at 19 sites and randomly assigned at 1:1 to TPLA or TURP groups . The patients will be followed up at 1, 3, 6, 12, 24 months after the procedure. Discussion The study will be the first multicentre clinical trial including 16 participating centres in China ,Italy, Switzerland and Poland with relatively large sample size 114. By comprehensively compare the safety and efficacy of TPLA with TURP in patients with BPH, especially concerning the improvement of lower urinary tract symptoms (LUTS) and complication incidence, the study will help to illustrate the clinical value of TPLA and provide a beneficial alternative treatment for BPH patients. Trial registration The study has been registered on Chinese Clinical Trial Registry (http://www.chictr.org.cn).Registration number: ChiCTR1900022739